The Gediz Supradetachment System (SW Turkey): Magmatism, Tectonics, and Sedimentation During Crustal Extension. Issue 4 (17th April 2019) - Asti, Riccardo; Faccenna, Claudio; Rossetti, Federico; Malusà, Marco G.; Gliozzi, Elsa; Faranda, Costanza; Lirer, Fabrizio; Cosentino, Domenico
Abstract: Unraveling the evolution of supradetachment basins developed in the hanging wall of low‐angle detachment faults may be an invaluable tool in reconstructing the tectonic evolution of highly extended terrains. These basins may record major regional tectonic events related to the exhumation of metamorphic core complexes, and the reconstruction of their evolution helps to quantify the amount of extension accommodated by such processes. Here we present stratigraphic and structural field evidence and micropaleontological constraints to the Neogene‐to‐Quaternary evolution of the supradetachment Gediz Graben that developed on top of the exhuming Central Menderes Massif (SW Turkey). This basin displays three different structural styles during its evolution: (i) it initiated as a ramp basin following the activation of the Gediz Detachment in the Middle Miocene, (ii) evolved as a half graben during the late Miocene following the activation of high‐angle brittle faults at its southern margin, and (iii) reached its final symmetric graben configuration in Late Pliocene (?)‐Quaternary times following the activation of its northern margin. New micropaleontological data document a short‐lived upper Tortonian marine episode in the basin, and major along‐strike variations in exhumation are documented on its southern margin. Our reconstruction shows how sedimentary basins originally formed in the hanging wall of detachment faults may eventually end up in tectonic contact with the mylonitic footwall. Finally, we highlight the importance of magmatism in localizing the deformation in highly extended terrains and in controlling the evolution of supradetachment systems. Key Points: The spatiotemporal ductile‐to‐brittle evolution of the Gediz detachment controls the tectonostratigraphic evolution of the Gediz Graben An upper Tortonian marine transgression is recorded in the sedimentary fill of the Gediz Graben Basins developed in the hanging wall of detachment faults may eventually end up in tectonic contact with the mylonitic footwall